Work on the mountain - Gonzalez, N. V. M. 1915-; Guzman, Richard R. (Diliman, Quezon City University of the Philippines Press, 1995)
Criticism on Philippines literature.
With: As in myth, the signs were all over / by Richard R. Guzman.
Includes bibliographical references.
Keywords: Philippine literature (English) -- 20th century -- History and criticism